2014
DOI: 10.1128/aem.03523-13
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical Characterization of a Novel l -Asparaginase with Low Glutaminase Activity from Rhizomucor miehei and Its Application in Food Safety and Leukemia Treatment

Abstract: A novel fungal gene encoding the Rhizomucor miehei L-asparaginase (RmAsnase) was cloned and expressed in Escherichia coli. Its deduced amino acid sequence shared only 57% identity with the amino acid sequences of other reported L-asparaginases. The purified L-asparaginase homodimer had a molecular mass of 133.7 kDa, a high specific activity of 1,985 U/mg, and very low glutaminase activity. RmAsnase was optimally active at pH 7.0 and 45°C and was stable at this temperature for 30 min. The final level of acrylam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(37 citation statements)
references
References 34 publications
4
30
0
3
Order By: Relevance
“…This is because the enzyme reduces more than 88% of the l -asparagine concentration from the initial feedstock. In last years, other works have dealt with this application of l -asparaginase, that can decrease the negative effects of acrylamide containing foods without impair their characteristics 3, 25, 26, 27, 28…”
Section: L-asparaginase Applicationsmentioning
confidence: 99%
“…This is because the enzyme reduces more than 88% of the l -asparagine concentration from the initial feedstock. In last years, other works have dealt with this application of l -asparaginase, that can decrease the negative effects of acrylamide containing foods without impair their characteristics 3, 25, 26, 27, 28…”
Section: L-asparaginase Applicationsmentioning
confidence: 99%
“…33,34 Because asparagine is also a key precursor in the formation of acrylamide, several studies have examined the potential of asparaginases from microbial sources to reduce the acrylamide content of processed foods, reviewed by Anese et al 35 and Zuo et al 36 These include the following selected observations. Blast cells lack the ability to synthesize the amino acid L-asparagine and rely on other sources of L-asparagine for protein synthesis.…”
Section: Asparaginases Inhibit Acrylamide Formation In Foodmentioning
confidence: 99%
“…Studies have demonstrated the production of l ‐ASNase with low l ‐GLUase activity from eukaryotic sources (Huang et al . ; Doriya and Kumar ), although some studies have shown that l ‐GLUase activity is important for the overall efficacy of treatment and serves as a positive modulator of l ‐ASNase activity in sub‐micromolar concentrations of asparagine in the serum of patients undergoing treatment (Anishkin et al . ).…”
Section: Discussionmentioning
confidence: 99%